Book Review: Glenn, M., Sullivan, B., Roche, M. & McDonagh, C. (2023) Action Research for the Classroom: A guide to values-based research in practice. Routledge. - Pete Boyd (Educational Journal of Living Theories)
This excellent book provides a practical guide for teachers and school leaders interested in pursuing professional inquiry or action research within their classrooms and schools. The distinctive feature and great strength of this practical guide is captured within its subtitle by the term ‘values-based research’. Previous practical guides have provided step-by-step support for teachers with their Action Research projects, some educational research books have proposed a focus on social justice, and other texts for teacher-researchers have proposed a valuesbased approach to research. However, this book provides particularly clear explanations, backed up with concrete examples, of how a teacher-researcher can integrate their professional values into an Action Research project. The book also provides a rationale for why this is an important challenge and how it can help a teacher to improve their professional, values-led practice as an educator.